Strategic Liquidity Mismatch and Financial Sector Stability - Silva, André F. (Review of Financial Studies, 2019)
[This paper examines whether banks strategically incorporate their competitors’ liquidity mismatch policies when determining their own and the impact of these collective decisions on financial stability. Using a novel identification strategy exploiting the presence of partially overlapping peer groups, I show that banks’ liquidity transformation activity is driven by that of their peers. These correlated decisions are concentrated on the asset side of riskier banks and are asymmetric, with mimicking occurring only when competitors take more risk. Accordingly, this strategic behavior increases banks’default risk and overall systemic risk, highlighting the importance of regulating liquidity risk from a macroprudential perspective.]